Evolutionary Conservation of the Early Axon Scaffold in the Vertebrate Brain. Issue 10 (13th August 2015) - Ware, Michelle; Dupé, Valérie; Schubert, Frank R.
<x xml:space="preserve">Abstract</x> The early axon scaffold is the first axonal structure to appear in the rostral brain of vertebrates, paving the way for later, more complex connections. Several early axon scaffold components are conserved between all vertebrates; most notably two main ventral longitudinal tracts, the tract of the postoptic commissure and the medial longitudinal fascicle. While the overall structure is remarkably similar, differences both in the organization and the development of the early tracts are apparent. This review will bring together extensive data from the last 25 years in different vertebrates and for the first time, the timing and anatomy of these early tracts have been directly compared. Representatives of major vertebrate clades, including cat shark, Xenopus, chick, and mouse embryos, will be compared using immunohistochemistry staining based on previous results. There is still confusion over the nomenclature and homology of these tracts which this review will aim to address. The discussion here is relevant both for understanding the evolution of the early axon scaffold and for future studies into the molecular regulation of its formation. Developmental Dynamics 244:1202–1214, 2015. © 2015 Wiley Periodicals, Inc.